EFFECT OF TRELLIS HEIGHT AND CUTTING FREQUENCY ON LEAF AND FRUIT YIELD OF FLUTED PUMPKIN (Telfairia occidentalis Hook F.) - U. P. Chukwudi; C. U. Agbo (Journal of Animal and Plant Sciences, 2014)
The horticultural management practices of trellis height and cutting frequency were evaluated to determine their effect on the yield of fluted pumpkin. Three bamboo trellis heights (non-trellised, 45 cm, and 90 cm) were combined with two cutting (uncut and bi-weekly) intervals to give six treatment combinations replicated three times in a 3 x 2 factorial in RCBD. The data collected were; length of the longest vine, number of leaves/plant, number of leaves/vine length of 40 cm, length and width of the central leaflet, vine diameter, marketable leaf yield by weight, days to first male and female flowering, number, weight, length, and circumference of the fruits. The data collected were subjected to analysis of variance (ANOVA) using GenStat Release 10.3DE statistical software. Trellis height of 90 cm was significantly (p<0.05) higher in most of the morphological parameters measured. Although there were no significant effects of trellis on number of days to anthesis, the result revealed improvement on the number of days to flowering as the trellis height increased. The trellised plants were significantly (p<0.05) higher than the non-trellised in total leaf yield/hectare. The uncut vines produced higher values in average fruit weight, fruit circumference, fruit length and total fruit weight/ha than the cut vines in both years. Trellis (staking) improved the vegetative phase, flowering and yield of T. occidentalis and should therefore, be introduced as an agronomic practice in fluted pumpkin production.
Keywords: Cutting frequency; Telfairia; staking; trellis height; yield